ANALISIS EFISIENSI PRODUKSI BUDIDAYA IKAN KARAMBA JARING APUNG DI TELUK AMBON DALAM - Arif, Desilina (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2020)
Background: Cultivation of floating net cages (KJA) in Ambon Dalam Bay (TAD), Ambon City began to be undertaken since the post-conflict period and when Indonesian grouper exports began to intensify, this effort was quite calculated. Fish farming is mainly aimed at maintaining grouper species (Chromileptes altiveles), tiger grouper (Epinephelus spp), Kuwe (Caranx sp), Beronang (Siganus spp) in ironwood cages and nets of a certain size, to maintain a number of seeds. fish, by feeding to harvesting. This cultivation has good prospects, wide open market and high economic value. Methods: Data were obtained from 33 groups of floating net cage fishermen who were carried out by census, namely all floating net cage fish farming groups as respondents from 2 sub-districts, namely Teluk Ambon and Teluk Baguala. Data analysis used the Cobb douglass production function with the help of the SPSS 17 program and analysis of the efficiency of the use of production factors. Results: The estimation results using the Cobb Douglas production function, showed significant variables, namely the area of ​​the cage, feed, and seeds had a positive effect on the production of floating net cage fish culture. Analysis of the efficient use of factors of production (ratio NPMXi / PXi) can be said to be inefficient, so the opportunity for development is wide open. Conclusion: The economic efficiency of floating net cage fish farming will be achieved if the technical efficiency and price efficiency of floating net cage fish farming is achieved. As the results of the analysis of technical efficiency and price efficiency analysis, obtained a ratio greater than one so that the economic efficiency achieved is greater than one, which means that the economic efficiency of fish farming has not reached the optimum point, it can be concluded that the floating net cage fish farming business is possible to do additional input to achieve an economic efficient level or the proportion of input can still be increased more